126k views
3 votes
Use the Chain Rule (Calculus 2)

Use the Chain Rule (Calculus 2)-example-1

1 Answer

7 votes

1. By the chain rule,


(\mathrm dz)/(\mathrm dt)=(\partial z)/(\partial x)(\mathrm dx)/(\mathrm dt)+(\partial z)/(\partial y)(\mathrm dy)/(\mathrm dt)

I'm going to switch up the notation to save space, so for example,
z_x is shorthand for
(\partial z)/(\partial x).


z_t=z_xx_t+z_yy_t

We have


x=e^(-t)\implies x_t=-e^(-t)


y=e^t\implies y_t=e^t


z=\tan(xy)\implies\begin{cases}z_x=y\sec^2(xy)=e^t\sec^2(1)\\z_y=x\sec^2(xy)=e^(-t)\sec^2(1)\end{cases}


\implies z_t=e^t\sec^2(1)(-e^(-t))+e^(-t)\sec^2(1)e^t=0

Similarly,


w_t=w_xx_t+w_yy_t+w_zz_t

where


x=\cosh^2t\implies x_t=2\cosh t\sinh t


y=\sinh^2t\implies y_t=2\cosh t\sinh t


z=t\implies z_t=1

To capture all the partial derivatives of
w, compute its gradient:


\\abla w=\langle w_x,w_y,w_z\rangle=(\langle1,-1,1\rangle)/(√(1-(x-y+z)^2))}=(\langle1,-1,1\rangle)/(√(-2t-t^2))


\implies w_t=\frac1{√(-2t-t^2)}

2. The problem is asking for
(\partial z)/(\partial x) and
(\partial z)/(\partial y). But
z is already a function of
x,y, so the chain rule isn't needed here. I suspect it's supposed to say "find
(\partial z)/(\partial s) and
(\partial z)/(\partial t)" instead.

If that's the case, then


z_s=z_xx_s+z_yy_s


z_t=z_xx_t+z_yy_t

as the hint suggests. We have


z=\sin x\cos y\implies\begin{cases}z_x=\cos x\cos y=\cos(s+t)\cos(s^2t)\\z_y=-\sin x\sin y=-\sin(s+t)\sin(s^2t)\end{cases}


x=s+t\implies x_s=x_t=1


y=s^2t\implies\begin{cases}y_s=2st\\y_t=s^2\end{cases}

Putting everything together, we get


z_s=\cos(s+t)\cos(s^2t)-2st\sin(s+t)\sin(s^2t)


z_t=\cos(s+t)\cos(s^2t)-s^2\sin(s+t)\sin(s^2t)

User Jesseplymale
by
5.7k points